Introduction to the special issue on time and HCI. Issue 1 (2nd January 2022) - Rapp, Amon; Odom, William; Pschetz, Larissa; Petrelli, Daniela
ABSTRACT: This special issue focuses on new perspectives of time within HCI research. We begin by explicating how HCI's views of time have broadened over the years, going beyond the traditional subjective-objective dichotomy. We describe how the HCI community was originally anchored to clock time, but more recently the field has begun to incorporate the existential, social, and cultural dimensions of time. We introduce the papers in this special issue by contextualizing them according to different research areas. We conclude by identifying open issues and opportunities that should be explored in future HCI research and practice.